2021
DOI: 10.1097/md.0000000000024123
|View full text |Cite
|
Sign up to set email alerts
|

Role of shear-wave and strain elastography to differentiate malignant vs benign subpleural lung lesions

Abstract: Elastosonography is a non-invasive diagnostic method to evaluate tissue stiffness. The aim of our study was to demonstrate the applicability and efficacy of elastosonography to differentiate benign vs malignant subpleural lung lesions compared to clinical, radiological and histological findings. We performed both strain and shear wave velocity (SWV) elastosonography on subpleural lung lesions. Moreover, we elaborated a composite score called ”elasto index”. Fourteen patients, 10 males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recent studies evaluated the role of elastosonography in differentiating benign vs. malignant consolidation. Our group reported a preliminary report on patients with subpleural consolidations that performed elastosonography evaluation; malignant lesions were characterized by higher values of tissue stiffness than benign ones [ 59 ].…”
Section: Pneumoniamentioning
confidence: 99%
“…Recent studies evaluated the role of elastosonography in differentiating benign vs. malignant consolidation. Our group reported a preliminary report on patients with subpleural consolidations that performed elastosonography evaluation; malignant lesions were characterized by higher values of tissue stiffness than benign ones [ 59 ].…”
Section: Pneumoniamentioning
confidence: 99%
“…9,12 When there is a critical reduction of alveolar air, the portion of pathological lung parenchyma acquires such a density as to be seen on ultrasound as a solid parenchyma, defined as the consolidation or hepatization process. 9,[13][14][15] The semiotics of LUS is mainly based on the study of alveolar-interstitial and pleural pathologies. 16 Hence, the reason why lung pathologies of vascular etiology cannot be evaluated by LUS, as they appear on ultrasound imaging as diffuse A-line pattern.…”
Section: Basics Of Lung Ultrasoundmentioning
confidence: 99%
“…At present, according to radiological technology, the most common instrumental diagnostic methods for differentiating malignant from benign lung lesions mainly include low-dose computed tomography (CT), positron emission tomography (PET), and magnetic resonance imaging, which help to improve the survival rate. 4 Bianconi et al 5 reported that deep learning was a viable approach for semiautomated segmentation of pulmonary nodules on CT scans and further found that the four form factors, ACO, AFL, KFL, and MPS, could be evaluated on lung nodules on CT scans and can improve the differential diagnosis between benign and malignant lesions. 6 Dual-energy spectral CT also has high accuracy in the differential diagnosis of benign and malignant pulmonary necrotic lesions.…”
Section: Introductionmentioning
confidence: 99%